Effect of vitamin B12 deficiency on olfactory function. Issue 10 (27th April 2016) - Derin, Serhan; Koseoglu, Sabri; Sahin, Cem; Sahan, Murat
Abstract : Background: Vitamin B12 plays a major role in the maintenance of central and peripheral nervous systems. Vitamin B12 deficiency may affect the spinal cord, brain, optic nerve, and peripheral nerve functions; however, the effect of vitamin B12 deficiency on olfactory function has not been studied, so our study aimed to investigate that. Methods: Thirty‐nine patients with low vitamin B12 levels and 34 controls were included in the study. All participants had detailed otorhinolaryngological examinations and laboratory tests. The Sniffin' Stick test was used for analysis of olfactory function. The 2 groups were compared for smell test results. Correlations of smell test results with demographic and laboratory data were investigated in the vitamin B12–deficient group. Results: The threshold discrimination identification scores were (mean ± standard deviation) 28.04 ± 5.58 and 35.10 ± 2.84 in the vitamin B12–deficient and control groups, respectively ( p < 0.001). In the vitamin B12–deficient group, hyposmia and anosmia were evident in 56.4% and 5.1% of the patients, respectively, but no subjects in the control group had olfactory dysfunction ( p < 0.001). Correlation analysis showed that age and odor identification score showed a negative correlation ( p < 0.001); however, there was a positive correlation between threshold, discrimination and identification (TDI) score and vitamin B12 levels. Conclusion: In this study, we showed for the first time that olfactory dysfunction may be present in patients with vitamin B12 deficiency. Apart from a negative correlation of age with odor identification score, none of the other parameters studied showed correlations with olfactory dysfunction.